2016
DOI: 10.1021/acs.biomac.6b01235
|View full text |Cite
|
Sign up to set email alerts
|

Smart Polymeric Hydrogels for Cartilage Tissue Engineering: A Review on the Chemistry and Biological Functions

Abstract: Stimuli responsive hydrogels (SRHs) are attractive bioscaffolds for tissue engineering. The structural similarity of SRHs to the extracellular matrix (ECM) of many tissues offers great advantages for a minimally invasive tissue repair. Among various potential applications of SRHs, cartilage regeneration has attracted significant attention. The repair of cartilage damage is challenging in orthopedics owing to its low repair capacity. Recent advances include development of injectable hydrogels to minimize invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
129
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(133 citation statements)
references
References 360 publications
3
129
0
1
Order By: Relevance
“…In the case of physical crosslinking, hydrogels have transient junctions that arise either from polymer chain entanglements or physical interactions such as ionic interactions, hydrogen bonds, hydrophobic interactions, or crystal formation . In chemical crosslinking, the junctions are permanent as a result of various chemical reactions, like radical polymerization, Michael addition, Schiff‐base reaction, photo‐polymerization, enzyme‐catalyzed polymerization, azide‐alkyne cycloaddition reactions . While chemical crosslinking results in higher stability and mechanical strength of hydrogels, there is a need of chemical modification or addition of crosslinking entities in vivo .…”
Section: Characteristics Of Hydrogelsmentioning
confidence: 99%
“…In the case of physical crosslinking, hydrogels have transient junctions that arise either from polymer chain entanglements or physical interactions such as ionic interactions, hydrogen bonds, hydrophobic interactions, or crystal formation . In chemical crosslinking, the junctions are permanent as a result of various chemical reactions, like radical polymerization, Michael addition, Schiff‐base reaction, photo‐polymerization, enzyme‐catalyzed polymerization, azide‐alkyne cycloaddition reactions . While chemical crosslinking results in higher stability and mechanical strength of hydrogels, there is a need of chemical modification or addition of crosslinking entities in vivo .…”
Section: Characteristics Of Hydrogelsmentioning
confidence: 99%
“…Hydrogels are physically or chemically cross‐linked polymer networks, which contain a large amount of water . The resulting soft elastic materials are suitable for applications in tissue engineering, medical devices, drug delivery, or artificial muscles .…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels are physically or chemically cross‐linked polymer networks, which contain a large amount of water . The resulting soft elastic materials are suitable for applications in tissue engineering, medical devices, drug delivery, or artificial muscles . Small molecule crosslinkers are particularly interesting for such hydrogels because their size, rigidity, charge state, and noncovalent interactions can control the elasticity, mechanical strength, and water binding efficiency of the hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…The suitability of a hydrogel for a given application depends on the mechanical properties that are affected by the environmental conditions such as temperature, pH level and ionic strength, magnetic and electric fields as well as the monomer type and crosslinking agents. [7][8][9] Among various types of hydrogels, poly acrylate polymers such as poly acrylic acid (PAA), with distinctive absorptivity properties, have the most versatile structure to enhance their practical utility in everyday life applications such as filtration, water remediation, diapers and hygiene products, cosmetics, wound dressings, medical waste solidification and metal ion removal. [10][11][12][13][14] From extensive studies evaluating different properties of PAA hydrogels, such as swelling, 15 adhesion, 16 diffusion, 17 physico-chemical 18 and mechanical 19 properties, it has been revealed that the greatest concern about these types of hydrogels is their poor mechanical properties.…”
Section: Introductionmentioning
confidence: 99%